Chapter Ships and Trade: The Role of Public Navigation in Renaissance Venice - MONTEMEZZO, STEFANIA (Atti delle «Settimane di Studi» e altri Convegni, 2019)
The paper aims at understanding the role that public navigation played for the Venetian merchant firms in the Renaissance. Thanks to the use of accountability, two case studies will be analysed to understand the involvement of private traders in the State galley system and their impact on the operations of the city's business in the late 15th century.